The Impact of Digital Accounting Literacy and Learning Resilience on Accounting Knowledge Among Accounting Students at IT&B Campus, Medan - Adi Harianto; Hou, Amin; Mega Sanjaya; Ratih Amelia; Chaniago, Sabaruddin (Journal of Finance Integration and Business Independence, 2024)
This study seeks to examine the impact of accounting digital literacy and learning resilience on the accounting knowledge of students at the Medan IT&B Campus. In the digital age, proficiency in technology and adaptability in a demanding learning environment are crucial elements for enhancing accounting learning results. This research employs a quantitative methodology via a survey technique. Data was gathered through the distribution of structured questionnaires to students enrolled in the Accounting program at the Medan IT&B Campus. The research sample comprised 75 students chosen by the proportional stratified random selection technique. The data analysis method included multiple linear regression utilizing Smart PLS software. The findings indicated that digital literacy in accounting positively and significantly influences students' accounting knowledge. This underscores that proficiency in digital technologies enhances the comprehension of accounting principles. Moreover, cultivating resilience substantially enhances students' accounting knowledge, underscoring the significance of tenacity and the capacity to surmount challenges throughout the educational journey. Both variables concurrently exert a significant impact on elucidating the level of accounting knowledge among students at the Medan IT&B Campus. This study offers a pragmatic contribution to educational institutions in formulating learning techniques that incorporate digital literacy and enhance students' learning resilience. The practical consequences encompass curriculum refinement, augmentation of technological facilities, and the formulation of technology-driven pedagogical approaches to cultivate exceptional accounting graduates equipped to confront difficulties in the digital age